Oxygen vacancies induced DX center and persistent photoconductivity properties of high quality ZnO nanorods. (18th April 2016) - Xie, Yong; Madel, Manfred; Feneberg, Martin; Neuschl, Benjamin; Jie, Wanqi; Hao, Yue; Ma, Xiaohua; Thonke, Klaus
Abstract: Ultraviolet sensors based on homoepitaxially grown ZnO nanorods were fabricated using clean room technology. We study the spectral dependence and frequency dependence of the photoresponse of these rods at different temperatures and ambient conditions. Whereas the response for above-bandgap light is fast, we find a slow response to light below band gap and clear signatures of persistent photoconductivity. These findings are explained by switching oxygen vacancies by light from nonconductive to conductive state, whereas the oxygen vacancies undergo a large lattice relaxation. The threshold photon energy for this process is found to be 2.6 eV at room temperature.